NGURAS SUMUR CAI KEDUNG: EKSPRESI RELIGI DAN IDENTITAS LOKAL DALAM KONTEKS PENGEMBANGAN PARIWISATA BUDAYA INDRAMAYU - Isad, Isad Suhaeb (UHN IGB Sugriwa Denpasar, 2026)
The Nguras Sumur Cai Kedung ceremony in Cikedung Lor Village, Indramayu, represents a local tradition that integrates spiritual, social, and ecological values within the community. This ritual is not merely a physical act of cleansing a water source but also a symbolic form of respect for nature and ancestral heritage. This study aims to explore the symbolic meanings and cultural values embedded in the Nguras Sumur ritual, as well as its relevance to the development of cultural tourism based on local wisdom. Using a mini-ethnographic approach, data were collected through direct observation and interviews with traditional leaders and community participants. The findings reveal that the ritual expresses the collective identity of the Cikedung community as guardians of harmony between humans and nature. Moreover, the tradition has the potential to be developed into a sustainable religious-cultural tourism attraction while preserving its inherent spiritual and social values.